You are my pride, my holy mother tongue! - Tulegenova Dilfuza Ergash kizi (Zien Journals, 2022)
Language is the spiritual wealth of a nation. Language is not only a means of communication - but also the culture, customs, way of life, history of a nation. Respect for the languages of different peoples, in turn, promotes mutual understanding and communication. And for languages to survive, they need to be supported. It is because of language that humanity is proud to belong to one nation or another. Recognition and respect for all languages is the only guarantee of peace. That is why every nation strives to preserve its language. Scientists estimate that at least one million people need to speak a language to survive. However, there are only 250 such languages in the world. Of course, the Uzbek language is one of the 250.
Keywords: mother tongue; Uzbek language; Self-awareness; nations